Plague in the 21st Century: Global Public Health Challenges and Goals - Hinnebusch, B. Joseph (National Institute of Allergy and Infectious Diseases, NIH, 2010)
Yersinia pestis, the Gram-negative bacterial agent of plague, is a zoonotic pathogen that primarily infects wild rodents and is transmitted by fleas. Y. pestis is one of the most invasive and virulent bacterial pathogens and has caused devastating pandemics, including the Black Death of 14th century Europe. The last plague pandemic began in Asia in the last half of the 19th century and lingered well into the 20th century, causing tens of millions of deaths as it spread across the world.